The Effectiveness of Educational Game Applications in Enhancing Learning Motivation Among Elementary School Students in the Digital Era - Azzahra, Putri Latiffa; Khaira, Alesha (International Journal Education and Computer Studies (IJECS), 2025)
The purpose of this study is to assess the degree to which educational game apps increase the learning motivation in elementary school students with regard to the occurrence of digitization. The study, using a mixed methodology, was conducted in 5 elementary schools with 150 students, 15 teachers, and 5 school principals. Three questionnaires were issued with regard to the SYB schemes, structured observations, interviews and documents being drawn in order to obtain consistent data. The results indicate that the students are significantlyÂ more enthusiastic to learn, (d = 0.82). The best usage model was determined to be 15 to 20 min per trial, 2-3 trials per week. In terms of intrinsic motivation there were increases due to curiosity (∆+1.2), independence (∆+1.1) and willingness to take challenges (∆+1.4). Main factors supporting the implementation of learning through trainees include the presence of technological infrastructure (85%), teachers’ competences (79%), and the school system support. These results offer useful insight for the design of tech-based learning interventions at the elementary level, indicating the need for consistent implementation protocols and for school-developer partnerships to be forged.